Efficient Rendering Analysis for Converting 3D to 2D Cartoon Style - Hu, Tingkai (Transactions on Computer Science and Intelligent Systems Research, 2025)
This paper explores using non-photorealistic rendering (NPR) techniques in Blender to simulate a 2D cartoon aesthetic using 3D models. NPR has become increasingly helpful in various fields like animation, education, and games due to its special aesthetic style, which resembles 2D animations and is low-cost. This study investigates how NPR, including flat shading and tone flattening, can be applied in Blender to build an efficient and wonderful NPR workflow. A toon shader pipeline is constructed using Blender's node system on the material page of Blender. Specifically, the method involves many nodes in Blender, for instance, Diffuse Bidirectional Scattering Distribution Function (BSDF), Shader to RGB, ColorRamp, and Emission Shader nodes, which could help people create a stylized 2D effect on a 3D model. An experiment is conducted on an ice cream model that the author made to test the performance of this system. The result shows that this method can produce clear, visually appealing models with strong color contrast and cartoon-style aesthetics. At the same time, the approach simplifies the light environment and converts it to color bands, which is very efficient. However, it will also cause the loss of some geometric information in complex shapes, such as glass cups or objects like cars or motors. This method offers a practical solution for 2D stylized rendering and opens up the potential for applications in 3D to 2D animation, education, short video design, and conceptual art.